Proszę o pomoc

2√18 -6√50 +4√30 -3/4√18 +5√98


Odpowiedź :

[tex]2 \sqrt{18} -6 \sqrt{50} +4 \sqrt{32} - \frac{3}{4} \sqrt{18} +5 \sqrt{98 }=\\\\=2 \sqrt{9*2} -6 \sqrt{25*2} +4 \sqrt{16*2} - \frac{3}{4} \sqrt{9*2} +5 \sqrt{49*2 }=\\\\=2 \sqrt{9 }*\sqrt{2} -6 \sqrt{25 }*\sqrt{2} +4 \sqrt{16 }*\sqrt{2} - \frac{3}{4} \sqrt{9 }*\sqrt{2} +5 \sqrt{49 }*\sqrt{2}= \\\\=2*3*\sqrt{2} -6 *5*\sqrt{2} +4 *4*\sqrt{2} - \frac{3}{4} *3 *\sqrt{2} +5 *7*\sqrt{2}= \\\\=6\sqrt{2} -30\sqrt{2} +16\sqrt{2} - \frac{9}{4} \sqrt{2} +35\sqrt{2}=\\\\=-8\sqrt{2} - 2\frac{1}{4} \sqrt{2} +35\sqrt{2}= -10\frac{1}{4} +35\sqrt{2}=24\frac{3}{4 } \sqrt{2}[/tex]

Odpowiedź:

[tex]8\frac{3}{4} \sqrt{2} +4\sqrt{30}[/tex]

Szczegółowe wyjaśnienie:

2√18 -6√50 +4√30 -3/4√18 +5√98 =

= [tex]2*\sqrt{9*2} - 6 *\sqrt{25*2} +4\sqrt{30} - \frac{3}{4} \sqrt{9*2} +5\sqrt{49*2}=[/tex]

= [tex]2*3\sqrt{2} -6*5\sqrt{2} +4\sqrt{30} -\frac{3}{4} *3\sqrt{2} +5*7*\sqrt{2}[/tex] =

= [tex]6\sqrt{2} -30\sqrt{2} +4\sqrt{30} -\frac{9}{4} \sqrt{2} +35\sqrt{2}[/tex]  =

= [tex]-24\sqrt{2} +4\sqrt{30} -2\frac{1}{4} \sqrt{2} +35\sqrt{2}[/tex] =

= [tex]8\frac{3}{4} \sqrt{2} +4\sqrt{30}[/tex]